Tf-lipoplexes for neuronal siRNA delivery: A promising system to mediate gene silencing in the CNS - Cardoso, A. L. C. (2008)
http://www.sciencedirect.com/science/article/B6T3D-4TBXG8W-1/2/0126aa3460b30ae6bbcf04124c1c63dd